What Should History Learning in Practice look like? A Meta-Analysis Review - Hasan Hasan; Dedi Kuswandi; Zahid Zufar At Thaariq (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
History learning is always expressed in conceptualisation that is oriented towards memorising, remembering, memory and many others, so it is not uncommon to often become boring learning for students. Considering the development of information and communication technology that has currently occurred, the orientation of learning has changed, including on historical material. This study seeks to reveal how history learning should be done by teachers of the subject through a series of meta-analysis activities. Author collected various quantitative research results related to history learning solutions as an expression of empirical evidence of its successful implementation. The main conclusion is that history learning needs to emphasise (1) flipped learning in the classroom, (2) virtual reality, (3) instructional video, and (4) self-regulated learning. Therefore, this article can be used as an alternative reference in learning history.